Quality of life of patients with graft-versus-host disease (GvHD) post-hematopoietic stem cell transplantation - Sibéli de Fátima Ferraz Simão Proença; Celina Mattos Machado; Raquel de Castro Figueiredo Pereira Coelho; Leila Maria Mansano Sarquis; Paulo Ricardo Bittencourt Guimarães; Luciana Puchalski Kalinke
Abstract OBJECTIVE Assessing the quality of life of adult patients with hematological cancer in the 100 days after transplantation of hematopoietic stem cells and verifying whether the variable graft-versus-host disease (GvHD) is predictive of worse results. METHOD An observational correlational and quantitative study with 36 adult participants diagnosed with hematologic cancer who underwent hematopoietic stem cell transplantation from September 2013 to June 2015. RESULT The mean age was 37 years, 52.78% were female, and 61.11% were diagnosed with leukemia. Quality of life scores showed a significant impact between pre-transplantation and pre-hospital discharge, and also within the 100 days post-transplantation. The statistical analysis between the scores for the groups with and without GvHD showed a significant difference between the presence of the complication and worse results. CONCLUSION Quality of life is altered as a result of hematopoietic stem cells transplantation, especially in patients who have graft-versus-host disease.